Comparative performance of high-rate anaerobic reactors for biodegradation of soybean molasses - de Mello, Bruna Sampaio [UNESP]; Rodrigues, Brenda Clara Gomes [UNESP]; Sarti, Arnaldo [UNESP] (Elsevier, 2021)
Soybean molasses is a residue obtained at the industrial processing of soybean to produce the soy protein concentrate. This residue is the result of the extraction of sugars from de-oiled soybean meal, which viable alternative to its disposal might be the degradation by anaerobic digestion (AD). Thus, a comparative study was performed in two high-rate technologies (UASB and ABR reactors) to evaluate the start-up time and optimum HRT required for the AD of soybean molasses under similar loading operations. The lab-scale reactors were fed with soybean molasses for 134 and 103 days under ambient conditions, respectively. Initially, the UASB reactor was operated at an organic loading rate (OLR) of 0.28 kgCOD m−3 d−1 (HRT = 48 h), while ABR reactor of 0.43 kgCOD m−3 d−1 (HRT = 36 h). OLRs were improved by reducing HRT 48 to 12 h and increasing substrate concentration (COD of 500 to 6000 mg L−1) for six different OLR in both reactors. After the fast start-up period, the UASB reactor attained values of CODTotal and CODFiltered removal efficiencies of 80% and 88%, respectively at an HRT of 24 h (3.91 kgCOD m−3 d−1) whereas ABR reactor presented 95% (CODTotal) and 97% (CODFiltered) at HRT of 36 h (3.86 kgCOD m−3 d−1) for similar OLR. By reducing HRT, both reactors have shown granular sludge flotation (sludge washout) and lower COD removal efficiencies (<80%). The experimental results revealed that high-rate anaerobic configurations (UASB and ABR reactors) can be used for the anaerobic biodegradation of soybean molasses with removal efficiency and a short start-up period.
Keywords: ABR reactor; Anaerobic digestion; Soybean molasses; UASB reactor